2017
DOI: 10.1093/icc/dtx038
|View full text |Cite
|
Sign up to set email alerts
|

Target choice and unique synergies in global mobile telephony: a dyadic approach

Abstract: The success of acquisitions rests on detecting and realizing unique synergies between buyer and target through their dyadic relationships. We study the role of unique dyad-specific synergies in the selection of takeover targets in the global mobile telecommunications industry. Firms use their foresight to select specific targets: First, they lower integration costs by selecting geographically close targets. This effect is stronger when buyer and target are in the same country, but only if the market is not so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…There is an abundant literature on the antecedents of acquisitions, and numerous studies have found qualities such as industry similarity, firm strategic correspondence, and geographic and demographic similarity to spur acquisition behavior (Boschma et al, 2016; Capron and Shen, 2007; Claussen et al, 2018; Kaul and Wu, 2016; Rao et al, 2016). Some studies have also investigated the role of ownership structure, though solely from the perspective of the acquiring firm (Gomez-Mejia et al, 2018; Miller et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an abundant literature on the antecedents of acquisitions, and numerous studies have found qualities such as industry similarity, firm strategic correspondence, and geographic and demographic similarity to spur acquisition behavior (Boschma et al, 2016; Capron and Shen, 2007; Claussen et al, 2018; Kaul and Wu, 2016; Rao et al, 2016). Some studies have also investigated the role of ownership structure, though solely from the perspective of the acquiring firm (Gomez-Mejia et al, 2018; Miller et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Within the realm of M&A, some studies have envisioned similarity as strategic likeness to demonstrate that acquisitions within similar business domains outperform those spanning more disparate domains (Bauer and Matzler, 2014; Capron et al, 2001; Chatterjee, 1986; Datta, 1991; Lubatkin, 1987; Ramaswamy, 1997; Tanriverdi and Venkatraman, 2005). In a parallel vein, strategic similarities in industry, technology, or capability overlap have been used to predict the selection of which target to acquire (Berchicci et al, 2012; Claussen et al, 2018; Kaul and Wu, 2016; Valentini and Di Guardo, 2012; Villalonga and McGahan, 2005; Wang and Zajac, 2007).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquisitions are an important way in which acquirers obtain critical resources and capabilities in technology industries (Graebner et al, 2010; Higgins and Rodriguez, 2006; Ransbotham and Mitra, 2010). One stream of research within the long tradition of M&A studies has emphasized the importance of target selection, and the question of who buys whom has attracted increasing research attention (Capron and Shen, 2007; Claussen et al, 2018; Kaul and Wu, 2016; Schildt and Laamanen, 2006; Welch et al, 2020; Yu et al, 2016). Drawing on competence‐based perspectives, most research on target selection shows the relevance of resource and knowledge relatedness, yet acquirers can also face serious difficulties and costs of judging the technological resources and other capabilities of high‐tech ventures in the first place.…”
Section: Introductionmentioning
confidence: 99%
“… For a similar procedure that studies the selection of one choice (in their case, takeover target) from a large number of potential (but unrealized) choices, see Claussen et al (). …”
mentioning
confidence: 99%